Cell structure-impact property relationship of polypropylene/thermoplastic elastomer blend foams - A. Heidari; M. Fasihi (eXPRESS Polymer Letters)
The purpose of the present study was to investigate the effect of cellular structure on the impact strength of polypropylene/polyolefin elastomers blend foams produced by the continuous extrusion process. To create different cell sizes, two chemical blowing agents were employed: azodicarbonamide and sodium bicarbonate. Sodium bicarbonate created foams with bigger cell size and cell wall thickness than azodicarbonamide. The impact strength of the neat and blend foams were studied and correlated to the foam properties and structure. It was observed that the impact strength of blend foams was directly related to the concentration of polyolefin elastomers (POE). Increasing POE by up to 30 wt% increased the foam impact strength by more than 400%. On the other hand, Increasing POE content caused the cell size and cell wall thickness to be reduced. Moreover, an attempt has been made to establish a relationship between the impact strength and cellular structural parameters. It was found that in the blend foams with higher cell wall thickness the rough fracture of the cell walls was intensified and in turn, the impact strength of the foams improved further.